A qualitative study on aspects of consent for genomic research in communities with low literacy. - Bukini, D; Mbekenga, C; Nkya, S; Purvis, L; McCurdy, S; Parker, M; Makani, J (BioMed Central, 2020)
Background Low literacy of study participants in Sub - Saharan Africa has been associated with poor comprehension during the consenting process in research participation. The concerns in comprehension are far greater when consenting to participate in genomic studies due to the complexity of the science involved. While efforts are made to explore possibilities of applying genomic technologies in diseases prevalent in Sub Saharan Africa, we ought to develop methods to improve participants’ comprehension for genomic studies. The purpose of this study was to understand different approaches that can be used to seek consent from individuals with low literacy in Sub-Saharan African countries in genomic research to improve comprehension. Methods Using qualitative study design, we conducted focus-group discussions, in-depth interviews and participant observations as data collection methods. This study was embedded in a hospital based genomic study on Sickle Cell Disease at Muhimbili National Hospital in Tanzania. Thematic content analysis was used to analyse the transcripts and field notes. Results Findings from this study show that literacy level has little influence on understanding the research details. According to the participants of this study, the methods used to provide information, the language, and time spent with the study participants were the key factors influencing understanding. The availability of group sessions held before individual consent to allow for a detailed questions and answers format was agreed to be the best method to facilitate the comprehension. Conclusion The quality of the consenting process of participants will be influence by a number of factors. The type of research consented for, where the research will be implemented and who are the potential study participants are amongst the factors that need to be assessed during the consenting. Measures to improve participants’ comprehension need to be developed when consenting participants with low literacy level in genomic studies.